PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ALFAMART KOTA PALANGKA RAYA - Arifin, Muhammad Zainal; Azhari, Pikri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2017)
Service quality gives encouragement to consumer to tie a good association with a company. Good service will give an impact to decision of consumer to buy and also to the company itself. A good service quality is very important to create a consumer